Electron paramagnetic resonance and photoluminescence investigation of europium local structure in oxyfluoride glass ceramics containing SrF2 nanocrystals - Antuzevics, Andris; Kemere, Meldra; Krieke, Guna; Ignatans, Reinis (Elsevier B.V., 2017)
Different compositions of europium doped aluminosilicate oxyfluoride glass ceramics prepared in air atmosphere have been studied by electron paramagnetic resonance (EPR) and optical spectroscopy methods. X-ray diffraction (XRD) and transmission electron microscopy (TEM) measurements show presence of homogenously distributed SrF2 nanocrystals after the heat treatment of the precursor glass. Efficient Eu3+ incorporation in the high symmetry environment of glass ceramics is observed from the photoluminescence spectra. EPR spectra indicate Eu3+ → Eu2+ reduction upon precipitation of crystalline phases in the glass matrix. For composition abundant with Eu2+ in the glassy state such behaviour is not detected. Local structure around europium ions is discussed based on differences in chemical compositions. ----/ / /---- This is the preprint of the following article: A. Antuzevics, M. Kemere, G. Krieke, R. Ignatans, Electron paramagnetic resonance and photoluminescence investigation of europium local structure in oxyfluoride glass ceramics containing SrF2 nanocrystals, Optical Materials 72 (2017), which has been published at https://www.sciencedirect.com/science/article/abs/pii/S0925346717304731. This article may be used for non-commercial purposes in accordance with Elsevier Terms and Conditions for Sharing and Self-Archiving.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; Electron paramagnetic resonance; Luminescence; Oxyfluoride; Transparent glass ceramics; Europium ions